2018
DOI: 10.1080/17441692.2018.1516796
|View full text |Cite
|
Sign up to set email alerts
|

Maternal health services for refugee populations: Exploration of best practices

Abstract: The full scope of women's health needs is not necessarily addressed in refugee camps and after resettlement, particularly pregnancy and postnatal services. The aims of this research are to examine the maternal care services provided to refugee women in camps and after resettlement to the United States, and to analyse organisational successes and challenges in service provision. With this understanding, policies can improve service delivery for refugee women. We interviewed respondents from five organisations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…Africa is the most mentioned continent with 14 different countries, followed by Asia with 11 different countries. North America was mentioned once as a host country for refugees who lived in camps before and not as a country that hosts an RC [14]. The study that has the highest number of host country locations is the study of Hynes et al [15], where they studied refugee maternal mortality in 25 camps in 10 countries.…”
Section: Search Results and Publication Characteristicsmentioning
confidence: 99%
“…Africa is the most mentioned continent with 14 different countries, followed by Asia with 11 different countries. North America was mentioned once as a host country for refugees who lived in camps before and not as a country that hosts an RC [14]. The study that has the highest number of host country locations is the study of Hynes et al [15], where they studied refugee maternal mortality in 25 camps in 10 countries.…”
Section: Search Results and Publication Characteristicsmentioning
confidence: 99%
“…Additionally, the Embrace volunteers help alleviate many barriers women face in accessing and navigating pregnancy-related services, particularly as it relates to relationships and communication with providers during the pregnancy, birth, and postpartum periods ( 40 ). As highlighted by Khan and DeYoung ( 41 ), culturally sensitive programs and strategies such as these are needed to assist refugee women with accessing maternity services that can improve outcomes. Furthermore, prior studies have demonstrated that incorporating culturally sensitive strategies has been successful in addressing barriers, promoting perinatal health service use, and improving outcomes among pregnant women ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, those studies will need to conduct careful power calculations to ensure the sample sizes are adequate to detect statistically significant results. Additionally, as found by several studies, the lack of cultural awareness and receptiveness among providers to refugee women's beliefs and practices surrounding birth creates disconnects between patients and providers and feelings of fear and marginalization among refugee women ( 41 , 44 , 50 ). In addition to birth education for refugee women, Embrace works closely and establishes relationships with healthcare providers in the community whom refugee women regularly see.…”
Section: Discussionmentioning
confidence: 99%
“…Postpartum care within refugee camps can be widely variable depending on the location of the camp and possible proximity of clinics [64]. What is known though, is that the current refugee and migrant situation is almost unprecedented with the number of refugees that are in southern Europe, thus resources are minimal.…”
Section: Discussionmentioning
confidence: 99%